Impact of Water Table Variability and Seismic Activity on Landslide Stability: Insights from the Kuiyadaha Slope - Baral, Sanjay (Journal of Engineering Issues and Solutions, 2026)
Landslides are one of the most common and destructive natural hazards in mountainous regions, causing significant damage to infrastructure, property, and human lives worldwide. This study examines the sensitivity of water table fluctuation and seismic effect on stability of slope located on the left bank of the Chameliya River above the Mahakali Highway at Kuiyadaha village, Baitadi District, Nepal. The landslide was triggered by prolonged heavy rainfall and has continued to move gradually, especially during the monsoon season, causing damage to residential structures and indicating persistent slope instability. Laboratory direct shear tests on soil samples reveal moderate shear strength characteristics, with internal friction angles ranging from 15.58° to 18.43° and cohesion values between 9.29 and 11.45 kN/m2, which were used as input parameters for slope stability modelling in Slide2. The stability of the slope was evaluated using limit equilibrium methods under varying groundwater and seismic conditions to analyse the sensitivity of the Factor of Safety (FoS). The results show that slope stability decreases significantly under saturated conditions due to increased pore water pressure and reduced effective stress. Sensitivity analysis further indicates that increasing seismic coefficients substantially reduce the FoS, highlighting the destabilizing influence of seismic forces. Conversely, groundwater drawdown improves slope stability by lowering pore pressure and increasing effective stress. Overall, the findings demonstrate that slope stability is highly sensitive to both seismic loading and groundwater conditions, emphasizing the importance of integrating seismic hazard assessment and groundwater management in landslide mitigation strategies.